Therapeutic Effects of 17β-Estradiol on Pelvic Organ Prolapse by Inhibiting Mfn2 Expression: An In Vitro Study - Wang, Xiao-Qing; He, Rui-Ju; Xiao, Bing-Bing; Lu, Ye (Frontiers in Endocrinology, 2020)
Objective: To assess the effects of 17β-estradiol (E2) on proliferation, apoptosis, and protein expressions of fibroblasts at different concentrations and time intervals to reveal the mechanism of E2 in the treatment of pelvic organ prolapse (POP). Study design: The uterosacral ligament fibroblasts were collected from 7 POP patients for primary culture of fibroblasts. The culture media containing 0, 10-6, 10-7, 10-8, and 10-9 mol/L E2 were used for 24, 48, 72 and 96 h. Main outcome measures: The cells were collected for cell counting kit-8 (CCK-8), apoptosis, quantitative reverse transcription polymerase chain reaction (qRT-PCR), and Western blotting assays. Results: Compared with the control group, in the values of fibroblasts cultured in 10-8 mol/L E2 for 72 h, the proliferation, mRNA and protein expression of Mitofusin-2 (Mfn2) separately increased (P < 0.05), decreased (P<0.001) and decreased(P<0.001). However, the expression level of procollagen 1A1/1A2/3A1 and cyclinD1 markedly increased (P<0.001, all), which was consistent with the results of protein level. What’s more, the expression of estrogen receptor α(ERα), estrogen receptor β(ERβ) and G protein-coupled receptor 30(GPR30) were significantly increased in 10-8 mol / L E2 group. Conclusions: E2 can inhibit the progress of POP by inhibiting the expression level of Mfn2, as well as promoting expression of procollagens and proliferation of fibroblasts. This effect is time- and concentration-dependent. Only when the estrogen concentration reaches 10-8 mol/L, the therapeutic effect is the greatest after 72 h.